The management of public expenditure by the Eastern Cape Department of Education and Health (2007/8 to 2011/12) and compliance with the PFMA - Shabalala, Gloria Nokuthula (Research of GSB, 2018)
Good financial and expenditure management remains a central issue of every governmental agenda as it relates to how available government resources are utilised. Financial management has undergone many reforms as the public administration discipline changed its approach. The classical approach to public administration gave rise to bureaucracies who in turn were bloated and largely inefficient. The new approach to public administration, NPM sought to promote good financial management through adoption of private sector practices by the public sector. The NPM approach gained momentum in the 1980s and 1990s. Both developed and developing countries adopted the approach as a solution to existing inefficiencies and to reduce the size of government. SA also adopted the approach in 1995 resulting in the promulgation of the PFMA in 1999. The NPM approach devolved decision making by making management accountable for financial mismanagement and expenditure of resources under their control. As a developing country, SA faces limited resources which have to be allocated to escalating and increasing needs. The Medium Term Expenditure Framework highlights the twelve key priorities of government. Health and Education are top of the lists. These two priorities are allocated the lion's share of the budget each and every year. Therefore, it is crucial to analyse how this allocated budget is utilised by the two Departments. The research analysed expenditure management for the Department of Health and Education of Eastern Cape between 2007/8 to 2011/12 and compliance with the PFMA that regulates financial and expenditure management by national and provincial departments. This was done through analysis of unauthorised expenditure; irregular expenditure and fruitless and wasteful expenditure and its implications for service delivery. Challenges that prohibit the two departments from improving financial management and expenditure management are also analysed.